A New Approach: Determination of the Safe Surgical Margin in Pterygium Surgery - Dag, Yasar; Armutlu, Ayse; Acet, Yakup (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose In this retrospective study, we aimed to determine the safe surgical limit for excision of pterygium tissue. Therefore, we aimed to prevent excessive or incomplete normal conjunctival tissue excision during surgery in the coming years.Methods Autografted pterygium surgery was performed between January 2015 and April 2016, and the excised pterygium tissue was examined histopathologically. The files of 44 patients, who had not previously undergone any ocular surgery, who did not have an inflammatory disease and who continued to be checked for at least 1 year, were retrospectively examined. The distance (P-DSEM) from the excised pterygium tissue to the surgical excision margin was measured by a pathologist. Postoperative recurrence rates were evaluated according to this value. In this way, the clean surgical margin was determined.Results The mean age of the participants was 44.77 ± 12.70, and the mean follow-up time was 55.61 ± 16.38 months. Recurrence developed in 5 out of 44 patients (11.4%). The average recurrence duration was 51 ± 13.87 days. Distance to the average surgical margin was 3.88 ± 0.91 mm. The surgical distances of 5 patients with recurrence were 2, 2.5, 2, 3, and 3 mm, respectively. It was determined that recurrence was less as the distance (P-DSEM) from the tissue to the surgical excision margin increased (p = 0.001).Conclusions We found that the recurrence rate in pterygium surgery was linked to the clean surgical margin. When planning pterygium surgery, we believe that determining the amount of tissue to be excised before surgery will reduce recurrence rates.
Keywords: pterygium surgical distance; pterygium surgery; relapsed pterygium; pterygium; cornea